Case report: Sudden cardiorespiratory collapse in a healthy male after coronavirus disease 2019 vaccination at a vaccination center - Chan, Cze Ci; Lin, Chia-Pin; Chang, Chi-Jen; Chu, Pao-Hsien (Frontiers in Cardiovascular Medicine, 2022)
Introduction Since 2020, the number of coronavirus disease 2019 (COVID-19) cases continues to increase daily, and new vaccines were developed to prevent more deaths. Here, we report a case of a previously healthy 35-year-old male who had a cardiopulmonary arrest 2 minutes after receiving the Oxford- AstraZeneca (ChAdOx1 nCoV-19) COVID-19 vaccination. He was unconscious after successful resuscitation and then admitted to the intensive care unit for targeted temperature management. A coronary angiogram was performed after neurological recovery and showed severe stenosis at the proximal left anterior descending artery. Stenting was done and he was discharge. To the best of our knowledge, no similar case of sudden cardiorespiratory collapse immediately after COVID-19 vaccination has been reported. Our patient did not have any effort-related angina or dyspnea on exertion before this event. The sudden cardiorespiratory collapse was probably related to underlying coronary artery disease, complicated with a vasovagal event. We stress the importance of coronary angiography in out of hospital cardiac arrest patients after neurological recovery. In the era of COVID-19 vaccination, even though fatal adverse events following immunization are rare, heightened awareness of severe side effects needing medical attention is very important.